(untitled) (Archive of Conferences, 2022)
The main task of the BCH at the present stage is the formation and development of a person on the basis of biological knowledge who can competently behave in nature and society. This article is about how to fill the content of biological education with the social activity of students, which will allow them to apply the knowledge and skills acquired in the learning process in practice.